Evaluation of the Distal Periodontal Bone Defect Associated with Lower Third Molar Extraction - Pierantonio Bellini; Shaniko Kaleci; Giacomo Setti; Sara Cavecchia; Carlotta Bellesia; Matilde Ruozzi; Ugo Consolo (Applied Sciences, 2025)
Background: Dental impaction requires careful consideration prior to extraction. Factors influencing the decision to extract an impacted tooth include the depth of impaction, proximity to vital structures, patient age, systemic conditions, and compliance. The eruption of third molars often presents periodontal challenges for adjacent second molars, with studies identifying a link between third molar presence and periodontal defects. Orthopantomography (OPG) is the primary diagnostic tool, providing a low-radiation, quick, and comprehensive view of the dental arches. Computed tomography (CT) offers additional three-dimensional information for a more accurate anatomical evaluation. Objective: This study aimed to evaluate the periodontal status of the lower second molar after lower third molar extraction, considering both periodontal and orthodontic perspectives. Methods: Conducted at the University of Modena and Reggio Emilia, this study evaluated changes in the periodontal status of the lower second molar at least 12 months after lower third molar extraction. A total of 53 patients meeting the inclusion criteria underwent surgical extraction. Clinical and radiographic evaluations were performed, analyzing parameters such as impaction type, angulation, and preoperative conditions. Results: The results suggest reduced healing in cases involving horizontal impacted third molars, although the small sample size limits statistical significance. These results align with the existing literature emphasizing better healing outcomes in young individuals undergoing early extraction. Conclusions: This pilot study highlights the periodontal implications of lower third molar extraction and underscore the potential benefits of early intervention for certain impaction types. Future research with larger sample sizes and a more detailed analysis of complications could provide deeper insights into the periodontal and orthodontic consequences of third molar management.